Genomic Sequence Analysis of the Multidrug-Resistance Region of Avian Salmonella enterica serovar Indiana Strain MHYL - Lu, Yan (Microorganisms, 2019)
A series of human and animal diseases that are caused by Salmonella infections pose a serious threat to human health and huge economic losses to the livestock industry. We found antibiotic resistance (AR) genes in the genome of 133 strains of S. Indiana from a poultry production site in Shandong Province, China. Salmonella enterica subsp. enterica serovar Indiana strain MHYL had multidrug-resistance (MDR) genes on its genome. Southern blot analysis was used to locate genes on the genomic DNA. High-throughput sequencing technology was used to determine the gene sequence of the MHYL genome. Areas containing MDR genes were mapped based on the results of gene annotation. The AR genes bla(TEM), strA, tetA, and aac(6′)-Ib-cr were found on the MHYL genome. The resistance genes were located in two separate MDR regions, RR1 and RR2, containing type I integrons, and Tn7 transposons and multiple IS26 complex transposons with transposable functions. Portions of the MDR regions were determined to be highly homologous to the structure of plasmid pAKU_1 in S. enterica serovar Paratyphi A (accession number: AM412236), SGI11 in S. enterica serovar Typhimurium (accession number: KM023773), and plasmid pS414 in S. Indiana (accession No.: KC237285).